Perceptions on Competence by Design in urology - Wang, Peter (Zhan Tao); Chan, Ernest; Forster, Adam; Vergel De Dios, Jennifer; Sener, Alp; Dave, Sumit; Chahine, Saad (Canadian Urological Association Journal, 2018)
Introduction: The Royal College of Physicians and Surgeons of Canada has begun implementing Competence by Design (CBD). However, it is unclear how much urology trainees and faculty know about CBD, their attitudes towards this change, and their willingness to embrace and participate in this new model of training. Methods: This cross-sectional study was conducted through an online survey, which was administered to all trainees and faculty at Canadian urology programs prior to the implementation of CBD. The final survey consisted of eight demographic questions, 17 five-point Likert items, one visual analog scale question, 11 multiple-choice questions, and two open-ended questions. Results: A total of 74 participants (38 faculty and 36 trainees) across 12 universities responded, with a completion rate of 82.4%. This corresponded to an overall response rate of 20.5%. Overall, there was a lack of resounding enthusiasm towards this shift to CBD in urology. Although both trainees and faculty had overall positive perceptions of CBD on assessment, teaching, and readiness, most agreed that this transition will be costly and associated with increased requirements for time, funding, and administrative support. Furthermore, there were significant concerns regarding the lack of valid assessment tools and evidence for the validity of entrustable professional activities. Conclusions: While this survey has demonstrated an appreciation for the benefits of CBD, challenges are equally anticipated. CBD in urology will be a fertile research area; this study has identified several important educational questions regarding the model’s effectiveness and consequences, thus, providing collaborative opportunities among all Canadian programs.